PERISTILAHAN KERAJINAN TANGAN TRADISIONAL ANYAMAN MASYARAKAT DAYAK JANGKANG - Erliani, Yusta; Patriantoro, Patriantoro; Saman, Sisilya (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstrack The terminology of traditional woven handicrafts is a language communication component that contains the meaning and use of words in language. Traditional woven handicrafts are activities related to handicrafts in the form of plaits that still use traditional methods in their manufacture, ranging from materials and tools to motifs. This is the reason why researchers choose the traditional handicrafts of the woven Javanese Dayak. so that woven handicrafts are maintained. Jangkang Dayak is one of the Dayak sub-groups who live in the Jangkang Subdistrict, Sanggau District, which is a residential area of the Jangkang Dayak indigenous people. This study includes the terminology of traditional woven handicrafts, term forms, lexical meanings, cultural meanings, and text-based Indonesian language learning models for 2013 curriculum education units.The method used in this research is descriptive method with qualitative research forms. The techniques used in this study are observation, interview techniques, recording and recording techniques, and drawing / object designation techniques. While the tools used are questionnaires, stationery, recording tools, pictures / photographs, and field notebooks. Keywords: Terminology, handicraft, cultural meaning, and lexical meaning.